Half-Formed Modernism: Eimear McBride’s A Girl is a Half-Formed Thing - Ward Sell, Aran (Hungarian Journal of English and American Studies, 2020)
This paper positions Eimear McBride’s novel A Girl is a Half-Formed Thing (2013) at the vanguard of a resurgent modernism in the 21st-century Irish novel, in the wake of the 2007-08 financial crash. It asserts the value of experimental literature to a country which has awoken from a dream of late capitalist prosperity into a sobering confrontation with late capitalist crisis. McBride’s novel reproduces certain generic characteristics of the historical realism which was the dominant literary mode of Celtic Tiger Ireland. However, it also innovates: McBride’s new, fragmentary adaptation of Joycean stream-of-consciousness navigates its familiar themes through the internal states of its traumatized protagonist.